Literal translation from English and Malay in the written communication among Malay learners of French - Abdul Halim, Hazlina (2012)
This study intended to examine the literal translation from English and Malay in the written communication among Malay learners of French by applying Dörnyei’s (1995) definition of the literal translation. The study utilized qualitative and quantitative methods of data analysis. A total of 50 subjects participated in this study. The task was to complete a writing task of 150-200 words after 100 hours of French learning. The results indicated that Malay language played a more important part in the translation, where 163 elements of translation were found as opposed to 76 elements from English. Among the translations produced by the learners, 57 items were in the word form, 77 items in the phrase form and 105 items in the sentence form. The results of this study could be great help in the teaching of French to Malay learners by making them aware of literal translation already in their repertoire and by encouraging them to turn the translation more correctly.